``White Land``.new Russian closed-cycle nuclear technology for global deployment - Bowman, C. D. (Los Alamos National Laboratory, 1996)
A Russian technology called ``White Land`` is being pursued which is based on their heavy-metal-cooled fast spectrum reactor technology developed to power their super-fast Alpha Class submarines. These reactors have important safety advantages over the more conventional sodium-cooled fast breeder reactors but preserve some of the attractive operational features of the fast spectrum systems. Perhaps chief among these advantages in the current political milieu is their ability to generate energy from any nuclide heavier than thorium including HEU, weapons plutonium, commercial plutonium, neptunium, americium, and curium. While there are several scenarios for deployment of these systems, the most attractive perhaps is containment in submarine-like enclosures to be placed underwater near a coastal population center. A Russian organization named the Alphabet Company would build the reactors and maintain title to them. The company would be paid on the basis of kilowatt-hours delivered. The reactors would not require refueling for 10--15 years and no maintenance violating the radiation containment would be required or would be carried out at the deployment site. The host country need not develop any nuclear technology or accept any nuclear waste. When the fuel load has been burned, the entire unit would be towed to Archangel, Russia for refueling. The fission product would be removed from the fuel by ``dry`` molten salt technology to minimize the waste stream and the fissile material would be returned to the reactor for further burning. The fission product waste would be stored at New Land Island, their current nuclear test site in the Arctic. If concerns over fission product justify it, the long-lived species will be transmuted in an accelerator-driven system. Apparently this project is backed at the highest levels of MINATOM and the Alphabet Company has the funding to proceed.